Patient-Centred Dental Hygiene Care: Assessing Satisfaction and Quality in Preventive Treatments—A Cross-Sectional Study - Ali Sadiq; Zahra Masood; Hassan Yaqoob; Muhammad Karim; Farhan Raza Khan; Noorin Khan; Hamza Arshad (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate patient satisfaction with treatments provided by dental hygienists, and to explore demographic influences on patient perceptions. Method: The cross-sectional study was conducted from April to June 2018 at Aga Khan University Hospital, Karachi, and comprised patients having received dental hygiene treatments. Patient satisfaction was assessed using the validated Dental Satisfaction Questionnaire. Data was analysed using SPSS 23. Results: Of the 83 patients, 51(61.4%) were females and 32(38.6%) were males. The overall mean age was 38.3±14.7 years. All the 83(100%) patients acknowledged respect and carefulness during examinations as well as effective pain management. Accessibility and operational convenience were less favourably rated; 9(8.4%) and 6(7.2%), respectively. Improvements in treatment quality were suggested by 38(45.4%) participants, and 29(34.9%) expressed dissatisfaction with waiting times. Cost-effectiveness was negatively perceived by 40 (39.8%) patients. Age and gender significantly influenced perceptions of care quality, pain management and cost-effectiveness (p<0.01). Conclusion: The patients generally reported high satisfaction with communication and respect shown by dental hygienists. However, operational factors, like waiting times and treatment quality, required attention. Key Words: Patient satisfaction, Dental hygienists, Preventive care, Communication, Pain management, Patientcentred care, demographic influence.